2004
DOI: 10.1097/01.ogx.0000110276.92930.d0
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulectomy for Vulvar Vestibulitis

Abstract: This randomized, prospective study was performed to compare 2 techniques used to reduce the size of an enlarged uterus before vaginal hysterectomy or laparoscopically assisted vaginal hysterectomy (LAVH). Thirty patients scheduled to undergo vaginal hysterectomy or LAVH were randomized to have uterine reduction performed using either bisection/morcellation (group I, n ϭ 14) or myometrial coring (group II, n ϭ 16). The 2 groups were comparable in clinical and demographic characteristics, including preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It remains unclear as to the extent to which hyperinnervation may contribute to sustaining chronic pain after acute inflammation subsides. However, in cases of provoked vulvodynia (vulvar vestibulitis) characterized by proliferation of vestibular sensory axons [5, 6, 34], excision of the tissue containing the abundant fibers provides pain relief in up to 80% of the cases [7, 13]. While this procedure does more than simply eliminate numbers of peripheral axons, it is consistent with the idea that hyperinnervation is a contributing factor in some chronically painful conditions.…”
Section: Discussionmentioning
confidence: 68%
“…It remains unclear as to the extent to which hyperinnervation may contribute to sustaining chronic pain after acute inflammation subsides. However, in cases of provoked vulvodynia (vulvar vestibulitis) characterized by proliferation of vestibular sensory axons [5, 6, 34], excision of the tissue containing the abundant fibers provides pain relief in up to 80% of the cases [7, 13]. While this procedure does more than simply eliminate numbers of peripheral axons, it is consistent with the idea that hyperinnervation is a contributing factor in some chronically painful conditions.…”
Section: Discussionmentioning
confidence: 68%
“…18,[26][27][28]52,53,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] There was insufficient evidence to describe the size of the effect with certainty, due to risk of bias inherent in pain intervention studies without placebo controls. Case series of 1138 patients and randomized trials of 118 patients reported an effect of 31% to 100%, with a median of 79% for patients who reported at least some improvement to complete relief.…”
Section: Vestibulodynia Results: Surgical Interventionsmentioning
confidence: 99%
“…23,24 Surgery success rates vary from 40 to 100%. 25,26 Although comparison between these studies is limited by differences in the number of patients, the presence of associated symptoms, definition of success and duration of follow up, our results on TENS treatment appear as effective, in particular when compared with surgery, with the advantage of being conservative. Specifically for studies that addressed the efficacy of surgery, medical treatments at the time of surgery and the lack of a standardised technique are additional variables.…”
Section: Discussionmentioning
confidence: 96%